Antioxidant and cryoprotective effects of Amur sturgeon skin gelatin hydrolysate in unwashed fish mince. (15th August 2015) - Nikoo, Mehdi; Benjakul, Soottawat; Xu, Xueming
Highlights: Gelatin hydrolysates were effective in protecting protein oxidation and in preventing lipid oxidation. Gelatin hydrolysate inhibited the displacement of water molecules between the different compartments. Gelatin hydrolysate could act as both antioxidant and cryoprotectant in unwashed fish mince. Gelatin hydrolysate could serve as the functional ingredients to maintain the quality of seafood. Abstract: Antioxidant and cryoprotective effects of Amur sturgeon skin gelatin hydrolysates prepared using different commercial proteases in unwashed fish mince were investigated. Gelatin hydrolysates prepared using either Alcalase or Flavourzyme, were effective in preventing lipid oxidation as evidenced by the lower thiobarbituric acid-reactive substances formation. Gelatin hydrolysates were able to retard protein oxidation as indicated by the retarded protein carbonyl formation and lower loss in sulfhydryl content. In the presence of gelatin hydrolysates, unwashed mince had higher transition temperature of myosin and higher enthalpy of myosin and actin as determined by differential scanning calorimetry. Based on low field proton nuclear magnetic resonance analysis, gelatin hydrolysates prevented the displacement of water molecules between the different compartments, thus stabilizing the water associated with myofibrils in unwashed mince induced by repeated freeze–thawing. Oligopeptides in gelatin hydrolysates more likely contributed to the cryoprotective effect. Thus, gelatin hydrolysate could act as both antioxidant and cryoprotectant in unwashed fish mince.